The Effect of Mobile English Learning Center to Teacher's Ability, English Proficiency and Attitude of Students in Remote Areas - Simpol, Wanida; Praraksa, Phoom; Sinthong, Prakit; paulina, Paulina (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
Inequality in education is an important problem in Thailand especially English learning between urban and rural students that concerned teacher quality, socioeconomic status of students, and English learning support system that directly affects the quality of English learning. This research aimed to develop teachers' ability in teaching English, English proficiency and attitude of primary students in Loei Primary Educational Service Area Office 2 where located in the remote area of Thailand using Mobile English Learning Center based on activity based learning approach. The study conducted 2 phases in the academic year 2019 with the 157 affiliated schools comprising of 130 teachers and 1,482 students. The quantitative and qualitative data were collected through questionnaires, English skills assessment, observation, interview, and reflection meetings. Descriptive statistics were applied for quantitative data, Z-test and one sample t-test for hypothesis testing and content analysis for qualitative data. The result of this research indicated that the treatment affected teachers' ability in teaching English, English proficiency and attitude of the students with the statistical significance, and also achieved the student attitude toward English learning. The implication and recommendation were also discussed.